Motor and premotor cortices in subcortical stroke: proton magnetic resonance spectroscopy measures and arm motor impairment - Craciunas, Sorin C. (2013)
BACKGROUND: Although functional imaging and neurophysiological approaches reveal alterations in motor and premotor areas after stroke, insights into neurobiological events underlying these alterations are limited in human studies. OBJECTIVE: We tested whether cerebral metabolites related to neuronal and glial compartments are altered in the hand representation in bilateral motor and premotor areas and correlated with distal and proximal arm motor impairment in hemiparetic persons. METHODS: In twenty participants at >6 months post-onset of a subcortical ischemic stroke and sixteen age and sex-matched healthy controls, the concentrations of N-acetylaspartate and myoinositol were quantified by proton magnetic resonance spectroscopy ((1)H-MRS). Regions of interest, identified by functional MRI, included primary (M1), dorsal premotor (PMd), and supplementary (SMA) motor areas. Relationships between metabolite concentrations and distal (hand) and proximal (shoulder/elbow) motor impairment using Fugl-Meyer Upper Extremity (FMUE) subscores were explored. RESULTS: N-acetylaspartate was lower in M1 (p=0.04) and SMA (p=0.004) and myo-inositol was higher in M1 (p=0.003) and PMd (p=0.03) in the injured (ipsilesional) hemisphere after stroke compared to the left hemisphere in controls. N-acetylaspartate in ipsilesional M1 was positively correlated with hand FMUE subscores (p=0.04). Significant positive correlations were also found between N-acetylaspartate in ipsilesional M1, PMd, and SMA and in contralesional M1 and shoulder/elbow FMUE subscores (p=0.02, 0.01, 0.02 and 0.02 respectively). CONCLUSIONS: Our preliminary results demonstrated that (1)H-MRS is a sensitive method to quantify relevant neuronal changes in spared motor cortex after stroke, and consequently increase our knowledge of the factors leading from these changes to arm motor impairment.